UNDERSTANDING DIFFERENT MEASUREMENT SCALE OF EMPLOYEE ENGAGEMENT Relationship (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Employee engagement has become one of a  hot topic in human resource management  among the global workforce. The practitioners  and academicians identified that employee  engagement have a positive impact on individual  and organization performance by adoption  various scaling technique. The purpose of this  research is to bring out the general discussion  about the various measurements scaling adopted  by researchers to measure employee engagement  which is published in various reputed academic  journals. The study discussed six measurement  scales used by many researchers, and identified  the scale which is widely used.
Keywords: E m p l oy e e E n g a g e m e n t; Measurement; Scaling